Maternal Stress / Distress and Low Birth Weight, Preterm Birth andIntrauterine Growth Restriction - A Review - Rondo, Patricia H.C. (Current Women's Health Reviews, 2007)
In this article a PubMed (www.ncbi.nlm.nih.gov/entrez), ISI Web of Science (www.isinet.com/isi) and Lilacs(www.bireme.br) literature review was carried out from 1986 to 2005, to search for publications which assessed theassociations between maternal stress/distress and low birth weight (LBW), preterm birth and intrauterine growthrestriction (IUGR). The studies investigated have yielded different results. The reasons are probably related to theterminology of stress and distress (not yet standardized); utilization of different instruments and populations to evaluatethese psychological disorders; the fact that a considerable percentage of the studies did not use adequate sample sizes, andthat some of them were retrospective in design. The impact of stress/distress on preterm birth and LBW seems to be moreimportant than its impact on IUGR. According to the majority of the studies assessed in this review, women exposed toacute stress in early pregnancy and to distress (anxiety, depression, etc) in late pregnancy are at significantly increasedrisk of shortened gestation. In conclusion, interventions to prevent stress/distress have to start before conception.Appropriate programmes should be carried out to address the origins and effects of stress/distress to pregnant women, toimplement relevant preventive interventions.
Keywords: low birth weight